2013
DOI: 10.1111/aap.12010
|View full text |Cite
|
Sign up to set email alerts
|

Sodium molybdate prevents hypertension and vascular prostanoid imbalance in fructose‐overloaded rats

Abstract: (1) Fructose (F) overload produces elevated blood pressure (BP), hyperglycaemia, hypertriglyceridemia and insulin resistance, resembling human metabolic syndrome. Previously, we found altered vascular prostanoid (PR) production in this model. (2) Sodium molybdate (Mo), as well as sodium tungstate, causes insulin-like effects and normalizes plasma glucose levels in streptozotocin-treated diabetic rats. We studied the effects of Mo on BP, metabolic parameters and release of PR from the mesenteric vascular bed (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…NO, PGI2, ET, TXA2 are vasoactive substances secreted by vascular endothelial cells and are involved in the regulation of vascular tone and proliferation of vascular smooth muscle cells [37]. Notably, these factors are important factors in the development of hypertension and prostanoid imbalance [38]. Xu et al found that the NO and 6-keto-PGF1a levels were decreased and endothelia and TXB2 levels were increased in spontaneously hypertensive rats, which is consistent with our results [39].…”
Section: Discussionsupporting
confidence: 90%
“…NO, PGI2, ET, TXA2 are vasoactive substances secreted by vascular endothelial cells and are involved in the regulation of vascular tone and proliferation of vascular smooth muscle cells [37]. Notably, these factors are important factors in the development of hypertension and prostanoid imbalance [38]. Xu et al found that the NO and 6-keto-PGF1a levels were decreased and endothelia and TXB2 levels were increased in spontaneously hypertensive rats, which is consistent with our results [39].…”
Section: Discussionsupporting
confidence: 90%
“…Our current results support findings from a previous analysis of NHANES survey cycle data from 1999 to 2012, which found that Cs was associated with lower SBP and DBP [38], and results from a small epidemiological study of particulate matter (PM) constituents, which found negative associations between Mo and SBP/DBP [39]. Two studies in rat models also support that exposure to Cs [40] and Mo [41] may reduce BP. However, results from other studies have yielded different conclusions: two NHANES analyses (2009-2012 and 2011-2012 cycles) identified positive associations of Cs and Mo with high BP [36,42], and a study of aging men with metabolic syndrome found no significant Spearman correlation between urinary Mo and SBP or DBP [43].…”
Section: Discussionsupporting
confidence: 89%
“…Plasma molybdenum and other essential elements concentrations were detected by inductively coupled plasma mass spectrometry (Agilent 7700 Series ICP-MS; Tokyo, Japan) in the Ministry of Education Key Laboratory of Environment and Health at Tongji Medical College of Huazhong University of Science and Technology, as described in our previous study [32]. In the daily measurement, specimens from MetS cases and control subjects were randomly assayed.…”
Section: Measurement Of Plasma Essential Elements Concentrationsmentioning
confidence: 99%